An updated framework for characterizing patients with pediatric feeding disorder - Volkert, Valerie M.; Lukens, Collen T.; Silverman, Alan H.; Johnson, Laura; Sharp, William G. (Frontiers in Child and Adolescent Psychiatry, 2025)
Expert consensus previously established a framework for characterizing patients with pediatric feeding disorder (PFD) through a multidisciplinary case report form (CRF) methodology. Field testing of the PFD CRF and creation of a shared patient database represented next steps in the development of this clinical tool. The current study assessed the acceptability and feasibility of the PFD CRF through data collection across three feeding programs involved in the initial development of the CRF. A total of 80 patients completed multidisciplinary team evaluations and contributed data to the current evaluation of clinical implementation. Data analysis and feedback from end users (i.e., multidisciplinary care teams) subsequently guided CRF revisions. Results suggests the PFD CRF represents a feasible and practical method of common data collection across institutions, while also providing important insights into future research and dissemination efforts.